2017
DOI: 10.1192/apt.bp.113.011288
|View full text |Cite
|
Sign up to set email alerts
|

Supporting carers of people with dementia: What is effective?

Abstract: Carer stress is well documented, especially in those caring for individuals with dementia. A recommendation of all national dementia strategies is to provide excellent support and information to informal carers of people with dementia. NICE guidance suggests that a range of tailored interventions, including psychological input, psychoeducation and training courses, should be offered to reduce caregiver burden and stress, although good-quality outcome-based evidence is lacking. On the basis of a narrative revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…[40]. Telephone counseling has been found to be cost-effective in reducing depressive symptoms and burden as well as increasing self-efficacy caregivers of people with dementia [25,[41][42][43][44][45].…”
Section: Rationale For Development Of the Present Interventionmentioning
confidence: 99%
“…[40]. Telephone counseling has been found to be cost-effective in reducing depressive symptoms and burden as well as increasing self-efficacy caregivers of people with dementia [25,[41][42][43][44][45].…”
Section: Rationale For Development Of the Present Interventionmentioning
confidence: 99%
“…However, the results of these studies have to be considered cautiously, because only a few studies have designed the experiment on the basis of a RCT approach [23], and the available RCT-based studies used small sample sizes [58]. In addition to this limitation, the heterogeneity of the examined variables, such as duration of the intervention, physical exercise intensity, weekly dose of activity, as well as a broad range of used exercises, also make it difficult to generalize the results to a larger population [43,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, different supportive interventions for caregivers of relatives with dementia have been developed, including support groups, formal approaches to care, respite care, educational programs to perform daily caring tasks, combined interventions, and other multicomponent approaches (Alzheimer's Disease International, 2016;Gaugler and Kane, 2015;Sorensen et al, 2002;Rodriguez-Sanchez et al, 2013;Prick et al, 2015). However, these interventions usually show methodological difficulties, such as overlap among intervention types, lack of details of the interventions, lack of control groups, and insufficient clarity of outcome measures (Jackson and Browne, 2017). Moreover, these interventions usually report low rates of adherence, as they are carried out of home, requiring additional resources for the participants: leave the care recipient at home, the time needed to be invested to participate, attendance to the facilities, and time for trips to the facilities to participate in the intervention (Prick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, previous research has suggested that more physical exercise-based supporting strategies should be implemented (Farran et al, 2016a;Jackson and Browne, 2017). Therefore, this study sought to evaluate, whether an individual face-toface home-based physical exercise program that is directed to informal female caregivers and supervised by a trained staff is feasible and effective, and to determine the potential positive impact of this intervention on mental health (Madruga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%